1993
DOI: 10.1111/j.1600-0897.1993.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiendometrial Autoantibodies Are Generated in Patients With Endometriosis

Abstract: Our results show that autoantibodies reactive against endometrial antigens are present in patients with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…These results are inconsistent with those of others [11][12][13][14][15] serum IgG from endometriosis patients but not from fertile women without endometriosis reacted against endometrial antigens with MW of 26, 34, 42, 82, 94, 100, and 120 kDa, which were found exclusively in the endometrium or in implants of endometriosis patients. Gorai et al 14 found that sera from women with endometriosis as well as that from a small number of normal women without endometriosis showed immune reactivity against endometrial antigens with MW of 26, 34, and 42 kDa and that the frequencies of antibodies to these endometrial antigens were significantly higher in endometriosis patients than in normal control women. Rajkumar et al 13 were unable to identify any endometrial antigens with MW <34 kDa to which serum antibodies were present but demonstrated the presence of serum antibodies against a 34 kDa endometrial antigen only in patients with endometriosis.…”
Section: Discussioncontrasting
confidence: 90%
“…These results are inconsistent with those of others [11][12][13][14][15] serum IgG from endometriosis patients but not from fertile women without endometriosis reacted against endometrial antigens with MW of 26, 34, 42, 82, 94, 100, and 120 kDa, which were found exclusively in the endometrium or in implants of endometriosis patients. Gorai et al 14 found that sera from women with endometriosis as well as that from a small number of normal women without endometriosis showed immune reactivity against endometrial antigens with MW of 26, 34, and 42 kDa and that the frequencies of antibodies to these endometrial antigens were significantly higher in endometriosis patients than in normal control women. Rajkumar et al 13 were unable to identify any endometrial antigens with MW <34 kDa to which serum antibodies were present but demonstrated the presence of serum antibodies against a 34 kDa endometrial antigen only in patients with endometriosis.…”
Section: Discussioncontrasting
confidence: 90%
“…This supports a concept that endometriosis possesses an autoimmune nature (9,(11)(12)(13)17). PDIK1L is a protein kinase that will associate with CLP-36-interacting kinase and is widely expressed in many organs and tissues (18).…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have suggested that some autoAb-reactions are provoked in patients with endometriosis (9)(10)(11)(12). Accordingly, autoantibodies (autoAbs) as serum biomarkers for the diagnosis of endometriosis have been investigated: anti-a-enolase-autoAb was found to be useful (13); however, the sensitivity of anti-a-enolaseautoAb was just comparable to CA125.…”
mentioning
confidence: 97%
“…High levels of BLyS result in B lymphocyte production of a plethora of autoantibodies. These autoantibodies include antiendometrial, anti-DNA, antiphospholipid, and antinuclear antibodies [38], and two of them have been identified as antiendometrial autoantibodies against alpha 2-HS glycoprotein and transferrin [39]. Because transferrin functions as an iron transporter in the human body, a high transferrin level in peritoneal fluid could reflect a high iron level in peritoneal fluid in endometriosis patients [39].…”
Section: Chronic Niche Inflammation In Endometriosis Developmentmentioning
confidence: 99%